CHARACTERISTICS OF REPRODUCTIVE FUNCTION DISORDERS IN PATIENTS WITH ENDOMETRIAL HYPERPLASIA WITHOUT ATYPIA - Huseynova, Z.S. (World of Medicine and Biology, 2024)
The study involved 118 women who were divided into three groups: Group C – control, practically healthy women (50 women), Group I – women with endometrial hyperplasia and reproductive dysfunction (43 patients), Group Ⅱ – women with reproductive disorders and endometrial hyperplasia in combination with one of the other benign uterine pathologies (25 patients). Patients with an increased body mass index and advancing age were found to have a higher incidence of endometrial hyperplasia and reproductive dysfunction. In patients with endometrial hyperplasia, menstrual dysfunction was manifested by menometrorrhagia, which was accompanied by posthemorrhagic anemia. Reproductive dysfunction in patients with endometrial hyperplasia is characterized by infertility. In Group I, primary infertility predominates; in Group II, secondary infertility is more common, and infertility lasting more than 5 years is more frequent in Group II. Levels of estradiol were higher, and progesterone levels were lower compared to the control group. In the group with endometrial hyperplasia, changes in the hemodynamic parameters of the uterine arteries were observed: the systole-diastolic ratio, resistance index, and pulsation index in both arteries were lower than in the control group. When pregnancy occurred after treatment in patients with endometrial hyperplasia, no significant pathologies were observed during pregnancy, in its outcomes, or in the condition of the newborns. Timely assessment and contribute to pathogenetically based treatment and the realization of reproductive desires.